2019
DOI: 10.1021/acsearthspacechem.8b00181
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Divalent Cations on Dark Production of Hydroxyl Radicals from Oxygenation of Reduced Humic Acids at Anoxic–Oxic Interfaces

Abstract: Humic acids (HAs) are redox-active and can serve as either electron acceptors or electron donors to participate in multiple redox reactions. In nature water, HA can be intimately associated with divalent cations, such as Fe 2+ , Ca 2+ , and Mg 2+ , through a series of reactions that may in turn affect the redox reactivity of HA. Recent advances have demonstrated that the oxygenation of reduced HA in the dark can produce •OH at anoxic−oxic interfaces. However, little is known about the roles of the divalent cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 70 publications
0
23
0
Order By: Relevance
“…H 2 O 2 was verified as an intermediate, and CO 2 increases upon oxidation of DOC were measured . Recent work by Liao et al revealed that ·OH production in the presence of reduced humic acids is dramatically increased in the presence of Fe­(II), supporting Fe­(II) being the primary driver of ·OH formation in these systems …”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…H 2 O 2 was verified as an intermediate, and CO 2 increases upon oxidation of DOC were measured . Recent work by Liao et al revealed that ·OH production in the presence of reduced humic acids is dramatically increased in the presence of Fe­(II), supporting Fe­(II) being the primary driver of ·OH formation in these systems …”
Section: Introductionmentioning
confidence: 90%
“…17 Recent work by Liao et al revealed that •OH production in the presence of reduced humic acids is dramatically increased in the presence of Fe(II), supporting Fe(II) being the primary driver of •OH formation in these systems. 18 In other natural systems, the relative roles of Fe(II), DOM, and other potential reducing agents has also been studied. Aeration of anoxic lake water, as would occur during turnover cycles, caused light-independent formation of •OH up to 0.2− 4.5 μmol L −1 , which degraded the fungicide dimethomorph by 24−42% per turnover.…”
Section: ■ Introductionmentioning
confidence: 99%
“…A well-characterized Aldrich HA was selected as a model NOM compound. Because this particular HA was used in numerous other studies, ,, it was selected so that the findings of our experiments could be directly compared with previous observations. Chemically reduced HA prepared by a Pd–H 2 method described previously was used for all experiments to emulate the reduced state of NOM present at anoxic conditions.…”
Section: Methodsmentioning
confidence: 99%
“…96 In addition, several studies have identified oxicanoxic interfaces in natural environments as hotspots for dark HO˙formation when DOM and metal-based reductants (such as CuS) are present. 97,98 A recent study even observed the formation of ROS in the dark in oxic solutions containing Cl − ions, SRFA and CuIJII), thus interfering in the redox cycle of such systems. 99 Furthermore, the presence of different NOM types that exhibit increased binding affinities towards CuIJII), such as humic acids, 40,42,100 could enhance Cu x S dissolution.…”
Section: Dissolution Of Cu X S Nanoparticlesmentioning
confidence: 99%